Reactivity of Fe(II) Species Associated with Clay Minerals - Hofstetter, Thomas B; Schwarzenbach, René P; Haderlein, Stefan B (Environmental science & technology, 2003)
Mineral-bound Fe(II) species represent important natural reductants of pollutants in the anaerobic subsurface. At clay minerals, three types of Fe(II) species in fundamentally different chemical environments may be present simultaneously, i.e., structural Fe(II), Fe(II) complexed by surface hydroxyl groups, and Fe(II) bound by ion exchange. We investigated the accessibility and reactivity of these three types of Fe(II) species in suspensions of two different clay minerals containing either ferrous iron-bearing nontronite or iron-free hectorite. Nitroaromatic compounds (NACs) exhibiting different sorption behavior on clays were used to probe the reactivity of the various types of reduced iron species. The clay treatment allowed for a preparation of nontronite and hectorite surfaces with Fe(II) adsorbed by surface hydroxyl groups at the edge surfaces. Furthermore, hectorite suspensions with additional Fe(II) bound to the ion exchange sites at the basal siloxane surfaces were set up. We found that both structural Fe(II) and Fe(II) complexed by surface hydroxyl groups of nontronite reduced the NACs to anilines. An electron balance revealed that more than 10% of the total iron in nontronite was reactive Fe(II). Fe(II) bound by ion exchange did not contribute to the observed reduction of NACs. Reversible adsorption of the NACs at the basal siloxane surface of the clays strongly retarded NAC reduction, even in the presence of high concentrations of Fe(II) bound by ion exchange to the basal siloxane surfaces. Our work shows that in natural systems a fraction of the total Fe(II) present on clays may contribute to the pool of highly reactive Fe(II) species in the subsurface. Furthermore, this work may help to distinguish between Fe(II) species of different reactivity regarding pollutant reduction. Although structural iron in clays represents only a small fraction of the total iron pool in soils and aquifers, reactive Fe(II) species originating from the reduction of structural Fe(III) in clays may contribute significantly to the biogeochemical cycling of electrons in the subsurface since it is not subject to depletion by reductive dissolution.